2010
DOI: 10.3109/02688697.2010.505671
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and disadvantages of awake surgery for brain tumours in the primary motor cortex: institutional experience and review of literature

Abstract: Patients undergoing awake surgery for resection of brain tumours in the primary motor cortex (M1) are at high risk of developing new motor deficits. Thus, use of this procedure requires consideration of several important points, including the optimal modality to localise M1 on the affected side and the overall advantages and disadvantages of the procedure. In our experience with awake surgery for 21 brain tumours located in the M1 from January 2004 through October 2008, we found that functional magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To confirm this principle, we compared the results of fMRI with intraoperative brain mapping of M1, and found that this principle of symmetry in fMRI totally agreed with the results of brain mapping. [30] We therefore used this principle of symmetry in fMRI for the localization of M1 instead of brain mapping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm this principle, we compared the results of fMRI with intraoperative brain mapping of M1, and found that this principle of symmetry in fMRI totally agreed with the results of brain mapping. [30] We therefore used this principle of symmetry in fMRI for the localization of M1 instead of brain mapping.…”
Section: Methodsmentioning
confidence: 99%
“…Many investigators have reported the removal of brain tumors in language-related areas by awake surgery, but relatively few reports have analyzed awake surgery for brain tumors located in motor-related areas. [312132030] The present study performed preoperative fMRI and DTI with continuous monitoring of motor function during awake surgery for brain tumors in motor-related areas, namely the primary motor area (M1), premotor area (PMA), and primary sensory area (S1). Our goal was to analyze factors associated with the deterioration of motor function in a large series of patients to establish safe, awake craniotomy for these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have found incorporating fMRI activation volumes into our neuronavigational models for brain tumor surgeries to be helpful in ensuring a safe surgical trajectory and strategy for resection (Figure 3). While some investigators have reported that fMRI is the most reliable means of localizing functional motor areas [63], others contend that cortical stimulation alone is adequate to guide maximal safe glioma resection [64]. The utility of fMRI for brain tumor resection in the future will rely on the continued correlation and refinement of fMRI activation areas with intraoperative mapping techniques and establishing standardized paradigms for cortical stimulation [65].…”
Section: Applications Of Neuronavigation: Integration Of Functional Imentioning
confidence: 99%
“…Removal of brain tumors within eloquent brain regions can result in iatrogenic motor deficits, speech disorders, and complex cognitive deficits [2, 3]. However, for some tumors, including high grade gliomas, the extent of tumor removal is highly correlated with patient survival, pushing the surgeon to remove as much tumor as possible [2].…”
Section: Discussionmentioning
confidence: 99%